High-efficiency borohydride oxidation and oxygen reduction on titanium-supported Au(NiMo) catalysts for Alkaline fuel cells - Sukomol Barua; Aldona Balčiūnaitė; Jūratė Vaičiūnienė; Loreta Tamašauskaitė-Tamašiūnaitė; Eugenijus Norkus (Chemical Physics Impact)
In this research, we used a straightforward and cost-effective methodology to fabricate a three-dimensional nickel-molybdenum (NiMo) thin-layer coating, sparsely decorated with gold crystallites, on a titanium substrate (denoted as Au(NiMo)/Ti). The catalysts were prepared by depositing NiMo onto a Ti surface through a simple electrochemical deposition technique involving a dynamic hydrogen bubble template, followed by gold crystallite decoration via galvanic displacement. The prepared NiMo/Ti and Au(NiMo)/Ti catalysts were investigated as promising potential materials for alkaline fuel cells. The Au(NiMo)/Ti-3 catalyst with an Au:Ni:Mo molar ratio of 1:52.5:2.4 exhibited significantly higher electrocatalytic activity toward the oxidation of sodium borohydride and the reduction of oxygen compared to the NiMo/Ti with a Mo:Ni molar ratio of 1:7.8 to 1:24.3, and Au(NiMo)/Ti-2 and Au(NiMo)/Ti-1 catalysts with Au:Ni:Mo molar ratios of 1:50.1:5.5 and 1:51.2:7.5, respectively. Direct alkaline NaBH₄-H₂O₂ single fuel cell tests were conducted using the prepared NiMo/Ti-3 with Mo:Ni molar ratio of 1:24.3 and Au(NiMo)/Ti-3 catalysts as the anode materials. The investigation revealed that the peak power density of up to 162 mW cm⁻² was attained at 25°C with a current density of 202 mA cm⁻² and a cell voltage of 0.8 V, when Au(NiMo)/Ti-3 was employed as the anode catalyst. The highest Au mass-specific peak power density of 42.9 kW g⁻¹ was obtained at 55°C. The Au(NiMo)/Ti-3 catalyst demonstrated significantly higher activity and greater stability than the NiMo/Ti-3 catalyst. Overall, the NiMo/Ti and Au(NiMo)/Ti catalysts are promising materials for use as anodes in direct sodium borohydride fuel cells.